Impact of factors at admittance predicting intensive care unit mortality in critically ill cancer patients - Savran, Yusuf; Arikan, Rukiye; Comert, Bilgin (International Journal of Research in Medical Sciences, 2016)
Background: The aim of this study is to evaluate the prognostic factors at medical ICU admittance predicting intensive care unit (ICU) mortality in cancer patients. Methods: Retrospectively data of adult patients admitted to medical ICU of a 1200-bed university hospital during January 2012-December 2013 interval were analysed. The patients were divided into three groups; patients with solid tumor, patients with hematologic malignancy and patients without cancer. The study end point was ICU mortality. Results: 512 patients were identified; 374 patients without cancer, 89 patients with solid tumor and 49 patients with hematologic malignancy. Overall mortality rate in intensive care unit was 46% (n=236). The ICU mortality rate of patients with hematologic malignancy was significantly higher than patients with solid tumors (68.6% vs 53%; p<0.001) and patients without cancer (68.6% vs 39.8%; p<0.001). Logistic regression analysis showed high APACHE II score and the requirement for invasive mechanical ventilation (odds ratio [OR], 5.52; 95% confidence interval [CI], 2.10-14.53; p<0.001) at the time of intensive care unit admittance as independent risk factors for increased mortality. In addition, the requirement of renal replacement therapy(OR, 2.34; [CI: 1.44-3.80]; p<0.002) and vasopressors(OR, 1.67; [CI: 1.10-2.54]; p<0.02) at the time of intensive care unit admittance were detected as independent risk factors for increased mortality in cancer free group. Conclusions: In critically ill cancer patients; high APACHE II score and the requirement of invasive mechanical ventilation should be evaluated at the time of intensive care unit admittance, for these are strong predictors of increased mortality.